Composites reinforced with plant fibers for biomedical applications - Benavides Romo, Patricia Estefania (2019)
Natural fibers have acquired great interest in recent years for reinforcing composites with the aim of substitute the dependence of synthetic and glass fibers. In Ecuador, there is a potential field of natural fiber production because of its biological wealth that has positioned it within the richest countries of biodiversity in the world. From this situation arose the idea of a study with the objective to incorporate plant fibers in a polymer matrix to develop a composite, enhancing the mechanical and physical properties of their constituents, for the future use in biomedical application. Various biomedical applications, such as drug delivery systems, scaffolds for tissue regeneration, and injectable biomaterials, can be provided with the use of composites, with appropriate selection of their components and microstructure. In conclusion, aspects such as the physical and mechanical characterization of fibers and composites must be approached to approve the use of these composites in the biomedical field. Also, will be necessary to standardize the tests for plant fibers and reinforced composites with the fibers in study for future research.